Lessons in Designing Safety Nets - Aiyar, Swaminathan S.A.; Lateef, K. Sarwar; Subbarao, Kalanidhi (World Bank, Washington, DC, 2012)
This briefly examines some considerations when designing safety nets: a) local needs; b) financial and political sustainability; c) cost benefit analysis; and d) approach at targeting needy groups. Furthermore, it emphasizes that the poor must be included in productive activity, so that safety nets complement growth, as well as, the combination with long-term programs, that build human capital and transfer assets to the needy, thus raising growth potential. The note provides design guidelines and suggestions for the safety net selection, either through cash transfers, in-kind transfers, public works programs and credit programs. Certainly, the approach taken will be determined by the country's circumstances, be it the nature of poverty and external shocks, or fiscal and delivery constraints.